Surveyor and dasawisma training in housing database collection in Kampung Rawa Village - Wahyu Sejati; Ryan Faza Prasetyo; Giraldi Fardiaz Kuswanda; Avelina Nathania Bennediktus Suhardjo Pusoko; Yureana Wijayanti; Sri Wulandari (Community Empowerment, 2024)
The Kampung Rawa sub-district is part of an initiative aimed at enhancing the quality of settlements by structuring integrated residential areas. It is known as one of the most densely populated sub-districts, with a population density of 68,956.67 people/km2. The surveyor and Dasawisma training program aims to equip participants with knowledge on collecting data about backlogs and uninhabitable houses (RTLH) based on building reliability, thereby minimizing errors during implementation. Data collection involves visiting residents' homes to assess building conditions and completing a form integrated with the Jakarta Satu website. The outcome of this training is an improvement in the knowledge and skills of surveyors and Dasawisma in conducting backlog and building reliability surveys in the field. The training also resulted in the development of a module as a reference guide for surveyors in assessing building reliability.